Increasing Awareness of the Human Papillomavirus (HPV) Vaccine for Women 18–45 Years of Age - Alina Cernasev; Alexandria Grace Yoby; Tracy Hagemann (Women, 2023)
The human papillomavirus (HPV) vaccine prevents cancer and is highly effective; however, the uptake has been low in the United States of America (USA) and among the most vulnerable populations. A recent Center for Disease Control (CDC) report highlighted that approximately 13,000 new cases of cervical cancer are diagnosed each year in the USA. Although cervical cancer is considered treatable, especially when detected early, in the USA, approximately 4000 women die every year of cervical cancer. However, little is known about access and awareness among women in the USA. The objective of this article is to focus on the role played by clinical pharmacists in bringing awareness about the HPV vaccine. It offers recommendations to enhance the administration of the HPV vaccine. This rapid literature review revealed two significant themes: Disparities in healthcare access to the HPV vaccine among women and clinical roles in empowering women to access the HPV vaccine. This rapid review emphasizes the need for future research in enhancing awareness about HPV as a viable strategy for women. As an integral part of the healthcare team, pharmacists can significantly improve awareness and administer the HPV vaccine, yielding enhanced outcomes and cancer prevention.